Evaluating effects of meal delivery on the ability of homebound older adults to remain in the community via a pragmatic, two-arm, randomized comparative effectiveness trial: study protocol for the Deliver-EE trial - Kali S. Thomas; Kimberly P. Bernard; Melissa Clark; Laura Dionne; Alison Fisher; Emily Gadbois; Jill Harrison; Lisa Juckett; Julie Locher; Patricia Risica; Tamara Sequeira; Lucy Theilheimer; et al. (Trials)
Abstract Background As food insecurity and healthcare costs are linked, healthcare entities (i.e., providers, healthcare systems, insurers) are increasingly interested in identifying and providing solutions to address food insecurity among their patients. Home-delivered meals are one long-standing solution to address food insecurity among homebound older adults. However, there is limited evidence about what mode of delivery is most effective in promoting community independence, reducing healthcare utilization, and improving quality of life as well as how these outcomes may vary as a function of people’s preferences for how meals are delivered to them. Methods With extensive stakeholder input, we designed and implemented a pragmatic randomized comparative effectiveness study in which we will enroll 2300 older adults on waiting lists at home-delivered meals programs across the country and randomize them to receive for 6 months, either (1) weekday lunchtime meals delivered by a local volunteer or driver who also provides socialization and wellness checks or (2) biweekly delivery of 10 frozen meals to participants’ homes. Participant data will be combined with Centers for Medicare and Medicaid Services (CMS) data to calculate post-randomization institutional vs. community days. Baseline and 3-month surveys will evaluate secondary outcomes (e.g., food insecurity, loneliness, quality of life) and exploratory outcomes (e.g., nutritional risk). To examine heterogeneity of treatment effects, we will test for interactions between the two types of meal delivery and participants’ preferred mode of meal delivery as well as participants’ living arrangements. Discussion This research will be the first to prospectively evaluate the comparative effectiveness of the two predominant meal delivery options. The knowledge generated from this research will be of value to healthcare providers, health systems, payers, community-based organizations, older adults, and their families, because it will identify the mode of meal delivery that best meets homebound older adults’ needs and promotes community independence. In addition, the experience of working closely with stakeholders in designing and conducting this trial will be useful to researchers seeking to engage with stakeholders in the development and evaluation of complex social service interventions while balancing regulatory, resource, and human subjects research considerations. Trial registration ClinicalTrials.gov.  NCT05357261 . Registered on May 02, 2022